Seismic retrofit of RC beam-column joints using the MF-EBR strengthening technique - Coelho, M. (2011)
The strengthening technique based on the application of multi-directional laminates of CFRP (MDL-CFRP) simultaneously glued and anchored to the surface of the elements to be strengthened has been recently proposed. This technique was designated Mechanically Fastened and Externally Bonded Reinforcement (MF-EBR) and combines the fasteners from the MF-FRP technique with the externally glued properties from the EBR. With the aim of assessing the potentialities of this technique for seismic retrofitting, three interior RC beam-column joints were strengthened according to the MF-EBR technique and tested. This work presents the entire test program executed, including test configuration, results and corresponding analysis.